2016
DOI: 10.1038/srep24965
|View full text |Cite
|
Sign up to set email alerts
|

The utility of DNA metabarcoding for studying the response of arthropod diversity and composition to land-use change in the tropics

Abstract: Metabarcoding potentially offers a rapid and cheap method of monitoring biodiversity, but real-world applications are few. We investigated its utility in studying patterns of litter arthropod diversity and composition in the tropics. We collected litter arthropods from 35 matched forest-plantation sites across Xishuangbanna, southwestern China. A new primer combination and the MiSeq platform were used to amplify and sequence a wide variety of litter arthropods using simulated and real-world communities. Qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 58 publications
4
81
0
Order By: Relevance
“…On the contrary, samples from the tropics (feces of E. infrafasciatus from Africa and spider webs from South America) displayed a much lower taxonomic resolution generally corresponding to family level (Figure b). In megadiverse environments and regions, such as equatorial environments, our ability to identify sequences precisely (e.g., at species level) is indeed strongly restricted by relatively incomplete public databases (e.g., Cowart et al, ; Beng et al, ; Lopes et al, ; Stat et al, ). Our results therefore illustrate the role of completeness of public databases and the importance in investing into species inventories to better understand food web and species interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, samples from the tropics (feces of E. infrafasciatus from Africa and spider webs from South America) displayed a much lower taxonomic resolution generally corresponding to family level (Figure b). In megadiverse environments and regions, such as equatorial environments, our ability to identify sequences precisely (e.g., at species level) is indeed strongly restricted by relatively incomplete public databases (e.g., Cowart et al, ; Beng et al, ; Lopes et al, ; Stat et al, ). Our results therefore illustrate the role of completeness of public databases and the importance in investing into species inventories to better understand food web and species interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Although false negatives often occur for rare taxa (e.g., Ficetola et al, 2015), they are also produced when the affinity between primer and primer-binding sites during polymerase chain reaction (PCR) is low (e.g., Elbrecht & Leese, 2017a;Vamos, Elbrecht, & Leese, 2017), which in turn will determine amplification success and hence the taxonomic coverage of a given primer set. Although there is growing use of control samples to assess levels of false positives (De Barba et al, 2014;Beng et al, 2016;Corse et al, 2017;Galan et al, 2018), no post hoc bioinformatic procedures can identify false negatives. Two primary strategies have been adopted to maximize the taxonomic coverage of primer sets used in metabarcoding studies.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that metabarcoding can be used to identify arthropod taxa in bulk arthropod samples (e.g. Kocher et al, ; Liu et al, ; Morinière et al, ), and for example be applied to assess how arthropod diversity changes to different land‐uses (Beng et al, ). Metabarcoding has also been used to assess how invertebrates might leak DNA to their preservative ethanol which then potentially can serve as a mean to obtain sample diversity information (Erdozain et al, ; Hajibabaei, Spall, Shokralla, & Konynenburg, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that metabarcoding can be used to identify arthropod taxa in bulk arthropod samples (e.g. Kocher et al, 2017;Liu et al, 2013;Morinière et al, 2016), and for example be applied to assess how arthropod diversity changes to different land-uses (Beng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Invertebrate DNA metabarcoding is a recent approach to monitoring that can effectively characterize invertebrate communities at a faster and cheaper rate than traditional morphological taxonomic identification (Yu et al ; Ji et al ; Beng et al ). DNA metabarcoding workflows consist of simultaneously amplifying standardized DNA fragments from the total DNA extracted from an environmental sample (Taberlet et al ).…”
Section: Introductionmentioning
confidence: 99%